CBIS-based information system strategy analysis in order to improve service quality at the serdang post office using SWOT - Endang Supriyadi; Maya Sofiana; Redjeki Agoestyowati; Fika Aryani; Sukarni Novita Sari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
This study analyzes the strengths, weaknesses, opportunities and threats of the Serdang Post Office to achieve maximum results in the services offered by the Serdang Post Office, by identifying all resources and supporting courier services owned by the Serdang Post Office and analyzing strategic plans that must Serdang Post Office carried out in achieving the organizational goals that have been determined. This research, which is categorized as a qualitative description, uses the researcher as the key instrument in this study. Data collection techniques used include distributing questionnaires (questionnaires) and documentation from archives and other secondary data published by the Serdang Post Office. The results of data analysis with an external internal matrix have illustrated the position of the Indonesian Post Office in a position of growth and stability and in the SWOT quadrant diagram, the Serdang Post Office has the opportunity and strength which means that it can support aggressive growth policies so that it does not rule out the possibility that the postal services offered expanded its market share, especially to start taking into account the development of micro, small and medium enterprises that continue to grow as a new market share for postal services. Increasing the capacity of employees as one of the main elements for the company and the collaborative relationships between institutions that have been carried out or are to be carried out need special attention to maximize the performance of the Serdang Post Office.